The Use of Instagram as Media for Stunting Campaign: Analysis on Gen Z Knowledge - Lathifah Dzakiyyah Zulfa (Nusantara Science and Technology Proceedings, 2021)
The long-term impacts of stunting are very diverse, such as cancer, diabetes, anemia, or stupidity, and will interfere with the productivity of the individual itself. The right educational media is needed to raise awareness of the young generation so that changes in the mindset of choosing food (nutritional intake) can start now and prevent stunting in future offspring. Z generation students as samples were given education through Instagram uploads from the @ChangeTheCircle account with the tag #ChangeTheCircle, after previously being asked to do a pretest. The pretest-posttest scores' mean from the intervention and control groups were then tested for significance by using paired t-test. Not forgetting to see a difference in initial ability, the researcher tested the unpaired t-test and U test on the two groups' pretest and posttest. The intervention group (P <0.05) showed a significant difference between pretest and posttest scores while the control group did not. The difference in initial ability as measured through the comparison of pretest scores was counted insignificant, so there was no bias from the sample's initial knowledge in the control or intervention groups to the posttest results. The campaign on stunting issues through Instagram posts with the tag #ChangeTheCircle has an impact on the reader's ability to answer questions, indicating that this campaign has succeeded in increasing their knowledge of stunting.